An evaluation of three methods of typing organisms of the genus Proteus - Tracy, Oonagh (1972)
An assessment of three simple methods of typing Proteus strains is described. The methods chosen were biochemical typing, bacteriocine typing, and typing by means of the Dienes phenomenon. Dienes typing was deemed to be superior to biochemical typing and bacteriocine typing. A brief discussion on the relationship between the Dienes phenomenon and bacteriocine production is appended.